2016
DOI: 10.1210/jc.2016-2104
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Cancer Risk: The Rotterdam Study

Abstract: Context: In vitro and in vivo experiments have assigned both oncosuppressive and oncogenic properties to thyroid hormones. Population-based studies have found inconclusive results. Objective: We aimed to prospectively assess the relation between thyroid function and incident cancer in a population-based setting. Design, Setting, and Participants: The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
125
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 34 publications
7
125
4
2
Order By: Relevance
“…A recent cohort study of 5,886 female participants found that the highest FT4 tertile of FT4 level compared to the lowest FT4 tertile was associated with 1.14-fold increased risk of breast cancer. 29 However, this association was not statistically significant after excluding thyroid-altering medication. 29 We found no significant difference between thyroid hormone levels and breast cancer development in association with menopausal status even though the associations were stronger among postmenopausal women than in premenopausal women.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A recent cohort study of 5,886 female participants found that the highest FT4 tertile of FT4 level compared to the lowest FT4 tertile was associated with 1.14-fold increased risk of breast cancer. 29 However, this association was not statistically significant after excluding thyroid-altering medication. 29 We found no significant difference between thyroid hormone levels and breast cancer development in association with menopausal status even though the associations were stronger among postmenopausal women than in premenopausal women.…”
Section: Discussionmentioning
confidence: 91%
“…That study used a hospital diagnosis of thyroid disease based on the Danish National Patient Registry and was limited by lack of laboratory data. A recent cohort study of 5,886 female participants found that the highest FT4 tertile of FT4 level compared to the lowest FT4 tertile was associated with 1.14‐fold increased risk of breast cancer . However, this association was not statistically significant after excluding thyroid‐altering medication …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…33 In addition, the majority of prospective studies on thyroid analytes have indicated an association with BC risk, although there are still no conclusive results. 10,12,[34][35][36][37] Regarding our studied analyte fT4, our research group and another large prospective study have recently shown that high fT4 was associated with an increase in BC risk 10,37 but a smaller prospective study reported low fT4 to be related to an increased BC risk. 35 For TPO-Ab, cross-sectional studies have found a correlation between presence of TPO-Ab and BC, as reviewed by Hardefeldt et al, 32 and our previous study indicated that prediagnostic TPO-Ab positivity decreases BC risk.…”
Section: Discussionmentioning
confidence: 86%